If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10=1/4(8y-13)
We move all terms to the left:
-10-(1/4(8y-13))=0
Domain of the equation: 4(8y-13))!=0We multiply all the terms by the denominator
y∈R
-(1-10*4(8y-13))=0
We calculate terms in parentheses: -(1-10*4(8y-13)), so:We add all the numbers together, and all the variables
1-10*4(8y-13)
determiningTheFunctionDomain -10*4(8y-13)+1
Wy multiply elements
-40y(8+1
Back to the equation:
-(-40y(8+1)
-(-40y9=0
| 8x-7=7x, | | 2E(2n-1)-1=5 | | 15(1.50)+d=29.50 | | 3x+7=8x+14 | | 6x-6=4;x=2 | | 33w+7=19 | | 2E(2x-1)-1=5 | | 4.8x^2-13x-48=0 | | 2x+12=3x-13 | | (x+8)^2=196 | | 90c=120-60 | | X+(x/2-6)=42 | | 1/3x+1/5=-2(5/6x+3) | | -4=12p+10/2* | | 30-2x=-15 | | (3k/14)+25=22 | | 3x-25=88 | | 100=1.25^x | | (3x^-4)-(16x^-2)+1=0 | | 1.5x=12.5 | | 3x^-4-16x^-2+1=0 | | 6(w+4)=9w+6 | | 32+8y=32+4y | | 2x-5=4×+1 | | 121=-3x-4(-5x+8) | | 8x+10=64 | | Y=-8/5x+4 | | I2x-5I=3 | | 6^(x-4)=2 | | (4/(x-2))=(-6/(x+6))+(2/(x-2)(x+6)) | | 7-3(x+6)=8x | | 5x+4(3x-11)=-129 |